Use of contraceptive implants at 12 months in women who intended to undergo immediate versus delayed postpartum insertion following high-risk pregnancy - Termtem Waidee; Srinaree Kaewrudee; Panicha Wattanakamolchai; Jen Sothornwit (Korean Society of Obstetrics and Gynecology, 2023)
Objective To assess the correlation between the intention to undergo immediate versus delayed postpartum contraceptive implant insertion following high-risk pregnancy, and the proportion of utilization and adverse effects. Methods We conducted a retrospective cohort study of women who gave birth after a high-risk pregnancy (according to the criteria defined by the Society for Maternal-Fetal Medicine) and intended to use contraceptive implants. The participants were classified into two groups based on whether they underwent immediate or delayed insertion. The primary outcome was the proportion of utilization of contraceptive implants at 12 months postpartum. We performed multivariate analyses to determine the relationships between the timing of insertion, characteristics, and methods used. Results Of the 482 women classified as having high-risk pregnancies, 103 intended to use contraceptive implants (54 immediate and 49 delayed insertions). Women in the immediate group were more likely to use contraceptive implants than those in the delayed group at 6 (95.2% vs. 26.2%, P<0.01) and 12 months (92.7% vs. 26.2, P<0.01). A higher proportion of participants in the immediate group reported spotting and prolonged bleeding at 12 months (51.1% vs. 23.8%, P=0.01 and 26.8% vs. 7.1%, P=0.01; respectively). However, satisfaction at 12 months was higher in the immediate group than in the delayed group. Conclusion Intention to undergo implant insertion during the immediate postpartum period appears to improve the utilization of highly effective contraception. Patients who underwent immediate implantation experienced more spotting, prolonged bleeding, and dysmenorrhea. This study supports the recommendation to provide immediate postpartum contraceptive implants to women following high-risk pregnancies.